A study on customer satisfaction at shell petrol stations / Nor Hilmi Jaid - Jaid, Nor Hilmi (1998)
Retailing in Malaysia has been growing tremendously over last few years. The competitions among retailers are getting more fierce. This is the time for careful operations and retailers will find it more important than ever to develop new and clear directions to maintain their market share. Competitive pricing, store appearance, merchandises assortment and excellent customer servipes7 are just some areas retailers have to seriously consider. No wdays, retailers need to stay close to he customers to understand their needs and wants. As the research was entitled "Customer Satisfaction at Shell Petrol Stations", therefore the study will emphasize more on the. customers points of view and perceptions based on their experiences at Shell stations. During the study one set of questionaires has been distributed to the customers that petronized Shell petrol stations. The questionaires have been distributed to 100 respondents. The data obtained from the respondents has been analyzed through Stastical Program for Science Social (SPSS/PC). Cross tabulation method has been use in analyzing the data. Chi-square ( % 2) and degree of freedom (df) used in interpreting the data and hypothesis testing. The result of the research showed that customer service, location and well merchandised shot are important for customer satisfaction